Public administration of environmentally-oriented development of territories in the Arctic zone. Efficiency assessment - S. P. Vishnyakova; Ya. D. Vishnyakov (Вестник университета)
The article was prepared on the subject of ensuring the sustainable development of the territories in the Arctic zone on the environmental basis. The aim of the study is to develop a conceptual approach to assess the efficiency of public administration in the field of environmental development of territories in the Arctic zone, as the variety and importance of modern environmental risks constantly increase. Special, universal and general scientific methods of scientific cognition were used in the work. The article presents problems, conceptual approach and proposals to assess the efficiency of public administration of environmentally-oriented territorial development in the Arctic zone and improve environmental performance and ecological and economic efficiency of activities in the Russian Arctic region. The key tasks, constituent elements, objects and criteria for assessing the efficiency of this activity are outlined.